2014
DOI: 10.1177/0363546514536680
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Functional, and Morphological Evaluations of Posterior Cruciate Ligament Reconstruction With Remnant Preservation

Abstract: Transtibial PCL reconstruction with remnant preservation resulted in satisfactory clinical, functional, radiological, and morphological outcomes. The results of combined posterolateral rotatory instability were comparable with those for isolated PCL reconstruction with adequate PLC reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 64 publications
3
52
0
Order By: Relevance
“…[4][5][6][7][8][9] Compared with Song et al, who report a Lysholm score of 92 with a minimum of 80 points and a Tegner level of 6 in their longterm study, 25 our observation finds similar high-activity levels but confirms slightly lower and more frequent results in literature regarding Lysholm and IKDC scores between 2 and 6 years postoperatively 1,8,9,12,16,22 with comparable high patient satisfaction. 1,8,9,12,16,22 Analyzing the 15 month results of a full arthroscopic inlay technique, Mariani et al found an IKDC rating of A for effusion and range of motion, normal and nearly normal assessment in overall IKDC scores in 56% of cases, and a side-toside difference in arthrometry of 3.6 mm. 26 The biomechanical evaluation of arthroscopic versus open tibial inlay techniques yielded similar initial fixation strength for both groups.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[4][5][6][7][8][9] Compared with Song et al, who report a Lysholm score of 92 with a minimum of 80 points and a Tegner level of 6 in their longterm study, 25 our observation finds similar high-activity levels but confirms slightly lower and more frequent results in literature regarding Lysholm and IKDC scores between 2 and 6 years postoperatively 1,8,9,12,16,22 with comparable high patient satisfaction. 1,8,9,12,16,22 Analyzing the 15 month results of a full arthroscopic inlay technique, Mariani et al found an IKDC rating of A for effusion and range of motion, normal and nearly normal assessment in overall IKDC scores in 56% of cases, and a side-toside difference in arthrometry of 3.6 mm. 26 The biomechanical evaluation of arthroscopic versus open tibial inlay techniques yielded similar initial fixation strength for both groups.…”
Section: Discussionsupporting
confidence: 80%
“…Although laboratory investigations have obtained positive results with stable fixation and anatomic tunnel replication, no clear evidence of clinical superiority of a reconstruction procedure has been reported. 5,8,[11][12][13] Therefore, optimal surgical tunnel construction, 7,8,14,15 graft choice, 12,16,17 graft placement 13,[18][19][20][21] or single-bundle versus double-bundle procedures 6,22,23 are still debatable. Evolving trends in PCL surgery include an arthroscopic all-inside tibial-inlay technique, which combines the benefits of biomechanically improved graft position avoiding a transtibial killer turn and of a minimally invasive arthroscopic approach.…”
mentioning
confidence: 99%
“…Four studies demonstrated no difference in postoperative scores in patients treated with isolated PLC reconstruction versus those treated with combined PLC/cruciate ligament reconstruction 9 21 24 25. Similarly, there was no difference in postoperative scores in patients treated with isolated PCL versus those treated with combined PCL/other ligament reconstructions 26 27. Cartwright-Terry et al 12 reported a lower mean IKDC score in patients treated with combined ACL/PLC reconstructions (80) compared with those treated with isolated ACL reconstruction (87) at 2 years postoperatively, but scores did not differ at the preoperative or other postoperative times (1 and 5 years).…”
Section: Resultsmentioning
confidence: 99%
“…Biomechanical data argue in favour of anatomic ligament replication to restore optimal stability [5, 6, 9, 10, 22-25, 28, 32]. Clinical assessments following transtibial and tibial inlay techniques yield satisfactory and promising results [1,8,16,18,21,30,35]. Since several co-variables affect the long-term outcome of PCL reconstruction, the verification of predictive values that assure high patient satisfaction and pre-injury knee function hardly seems to be realistic.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the ideal management protocol is controversially discussed [18,29,33,35]. Optimal surgical tunnel construction [9,17,32], graft choice [18,19], graft placement [20,24,30] and single-versus double-bundle procedures [3,6,16] are still debatable, however. Correct graft tunnel placement has been identified as an essential factor influencing functional outcome and stability [4,10,22,28].…”
Section: Introductionmentioning
confidence: 99%